Worker Representation - Alex Bryson; John Forth (Institute of Labor Economics (IZA), 2022)
We define worker representation, identify the factors that determine demand for it among workers and employers, discuss difficulties in supplying worker representation, and reflect on the implications of worker representation for worker welfare and the behavior and performance of employers.
Keywords: J5; J51; J52; J53; J83; 330; worker representation; unions; collective bargaining; voice